Persistence of a dominant bovine lineage of group B Streptococcus reveals genomic signatures of host adaptation. (25th October 2016) - Almeida, Alexandre; Alves‐Barroco, Cinthia; Sauvage, Elisabeth; Bexiga, Ricardo; Albuquerque, Pedro; Tavares, Fernando; Santos‐Sanches, Ilda; Glaser, Philippe
Summary: Group B Streptococcus (GBS) is a host‐generalist species, most notably causing disease in humans and cattle. However, the differential adaptation of GBS to its two main hosts, and the risk of animal to human infection remain poorly understood. Despite improvements in control measures across Europe, GBS is still one of the main causative agents of bovine mastitis in Portugal. Here, by whole‐genome analysis of 150 bovine GBS isolates we discovered that a single CC61 clone is spreading throughout Portuguese herds since at least the early 1990s, having virtually replaced the previous GBS population. Mutations within an iron/manganese transporter were independently acquired by all of the CC61 isolates, underlining a key adaptive strategy to persist in the bovine host. Lateral transfer of bacteriocin production and antibiotic resistance genes also underscored the contribution of the microbial ecology and genetic pool within the bovine udder environment to the success of this clone. Compared to strains of human origin, GBS evolves twice as fast in bovines and undergoes recurrent pseudogenizations of human‐adapted traits. Our work provides new insights into the potentially irreversible adaptation of GBS to the bovine environment.